Fly ash – waste management and overview : A Review - Dwivedi, Aakash; Jain, Manish Kumar (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Fly ash (FA)-a coal combustion residue of thermal power plants has been regarded as a problematic solid waste all over the world. India has some of the largest reserves of coal in the world. Indian coal has high ash content and low calorific value. Nearly 73% of the country’s total installed power generation capacity is thermal of which coal-based generation is 90%. Some 85 thermal power stations, besides several captive power plants use bituminous and sub-bituminous coal and produce large quantities of fly ash. High ash content (30% - 50%) coal contributes to these large volumes of fly ash. Current annual production of Fly ash, a by-product from coal based thermal power plant (TPPs), is about 112 million tones (MT). Some of the problems associated with Fly ash are large area of land required for disposal and toxicity associated with heavy metal leached to groundwater. Fly ash, being treated as waste and a source of air and water pollution till recent past, is in fact a resource material and has also proven its worth over a period of time. The present paper reviews the potential applications for coal fly ash as a raw material: as a soil amelioration agent in agriculture, use, in highway embankments, in construction of bricks, as an aggregate material in Portland cement, filling of low lying areas etc in the manufacture of glass and ceramics, in the production of zeolites, in the formation of mesoporous materials, in the synthesis of geopolymers, for use as catalysts and catalyst supports, as an adsorbent for gases and waste water processes, and for the extraction of metals. Thus fly ash management is a cause of concern for the future. This article attempts to highlight the management of fly ash to make use of this solid waste, in order to save our environment. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>